BASIC ASPECTS OF THE SYSTEM OF MANAGEMENT OF EDUCATIONAL INSTITUTIONS IN THE COUNTRIES OF WESTERN EUROPE - M F Mizintseva (RUDN Journal of Economics, 2016)
In article features of system of management of institutions of higher education in Western European countries. Examines the competitive advantages of Western European universities, their market orientation, the role of accreditation in the universities of Western Europe, the system of remuneration and benefits for teachers. In addition, the analysis of the best higher educational institutions of Europe in the highly competitive global market of educational services. The conclusion that administrative experience by educational institutions of Western Europe has to be adapted to the Russian specifics is drawn. Special attention is offered to be paid on accreditation procedures, market orientation of higher education institutions, systems of the individual training programs, elements of electronic training and serious training of students for further scientific activity.